Managing Higher Education in Pandemic Era in the Challenge of Education Quality and Equity - B.M.A.S. Anaconda Bangkara; Endang Fatmawati; M. Tirtana Siregar; Vani Wirawan; Wisman Wisman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The article is to examine several pieces of evidence from previous studies to understand higher education governance in the crisis-era related to the challenges of achieving equal distribution of education quality. Data collection involves searching for many published articles, including journals, books, magazines, and websites that discuss higher education governance issues regarding quality and opportunity. The data analysis involves a comprehensive evaluation data coding system, critical interpretation, and comprehensive and high decision making. The data search is done with the help of technology, especially online data sources using keywords such as the quality of higher education, equal opportunity. Based on the findings, explanations, and discussions, we can summarize that the governance of higher education in the crisis era faces various challenges related to equity and the achievement of high quality. When a crisis occurs, the changes are significant, and they cannot carry out various obligations and intellectual rights so that they ignore the quality and equity of higher education. Therefore, this study recommends that high fences be managed by emphasizing finding solutions to address the challenges of service quality and equity by following guidelines and regulations in force in many countries. It is hoped that this study will become an essential input to solve the challenges of higher education afflicted by various crises. Keywords: Education Quality and Equity, Managing Higher Education, Education in Pandemic Era